Pengaruh Kompetensi Dan Kompensasi Calon Pekerja Migran Indonesia Terhadap Motivasi Untuk Bekerja Keluar Negeri - Fuadi Fuadi; Firli Agusetiawan Shavab; Budi Subakti (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This research was conducted to determine the effect of competence and compensation on motivation to work abroad by taking cases in the progressing CPMI at UPT BP2MI Serang through the Private To Private Placement Scheme, the type of research is explanatory using data collection techniques through questionnaires. The sampling technique used a probability sampling technique with a total of 86 respondents from 110 populations who were Candidates for Indonesian Migrant Workers (CPMI) who carried out the placement process at UPT BP2MI Serang. The data analysis method used in this research is quantitative data analysis. The conclusion of this study is that the CPMI Competence and Compensation has a positive and significant effect on the motivation to work for CPMIs who are processing at UPT BP2MI Serang through the Privat To Privat / P To P placement scheme.